1975
DOI: 10.1111/j.1365-2141.1975.tb01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Studies as a Prognostic Index in Acute Liver Failure

Abstract: A coagulation screen has been performed on 12 patients with acute liver failure. Six died and six recovered. All six fatal cases developed a haemorrhagic state with haemostatic failure. An attempt has been made to delineate the various mechanisms for the production of the coagulation defect. The significance of the different haematological parameters in assessing prognosis has been assessed. The study emphasizes the importance of the synthetic ability of the liver in determining survival prospects. A good cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 15 publications
3
31
0
2
Order By: Relevance
“…Bromsulphophthalein retention (fig 3) Although there appeared to be some correlation between BSP retention and factor VII in the 34 patients in whom (Dymock et al, 1975), but this study shows the assay to be of less value in chronic liver disease.…”
Section: Relationship Between Factor VII Levels and Other Tests Of Limentioning
confidence: 63%
See 2 more Smart Citations
“…Bromsulphophthalein retention (fig 3) Although there appeared to be some correlation between BSP retention and factor VII in the 34 patients in whom (Dymock et al, 1975), but this study shows the assay to be of less value in chronic liver disease.…”
Section: Relationship Between Factor VII Levels and Other Tests Of Limentioning
confidence: 63%
“…An artificial factor VII substrate is difficult to prepare. The discovery of a congenitally severe defect of factor VII in a colony of beagle dogs has facilitated limited clinical studies which have on factor VII shown that the assay is of great value in assessing r synthesis in the prospects of survival in acute liver failure following the (Dymock et al, 1975). As supplies of VII deficient Ki.…”
Section: Relationship Between Factor VII Levels and Other Tests Of Limentioning
confidence: 99%
See 1 more Smart Citation
“…The prothrombin activity is largely also used in score models, to define the degree of liver damage and to assess prognosis and, in fact, its abrupt reduction is associated with a lower life expectancy [42,[109][110][111], However, this test is unsatisfactory when used to assess individual life expectancy as it does not permit a differentiation of survivors from nonsurvivors [112], Among vitamin-K-dependent factors the evaluation of factor VII provided interesting results; in patients with acute hepatitis values of factor VII < 10% identified all patients who died of liver failure [27,44], Similar findings were obtained studying patients with liver failure followed up for approximately 2 months; factor VII values < 38% differentiated patients who died from survivors [113]. The evaluation of prekallikrein activity could also represent another interesting future laboratory approach to as sess prognosis of individual patients.…”
Section: Clotting Changes As Predictors Of Hemorrhage and Survivalmentioning
confidence: 99%
“…Among the vitamin-K-dependent factors, the study of factor VII. considering its short half-life, might turn out to be very useful, as it proved to be the most sensitive index of cell damage [44], As the method to assess prothrombin and factor VII activities is easy and cheap, these laboratory tests should be recommended to evaluate liver failure. Other laboratory tests such as AT III.…”
Section: Diminished Hepatic Protein Synthesismentioning
confidence: 99%